CLINICAL ASSESSMENT OF LIQUID NITROGEN CRYOTHERAPY IN MANAGEMENT OF ORF LESIONS IN GOATS - Joshi , D.O; Tank , P H; Vedpathak, H S; Karle, A S; Dhami , M A (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
A total of 16 clinical cases of orf in goats belonging to either sex having different age were divided into two groups: Group- I (10 Goats) given routine medicinal treatment like antiseptic dressing, antibiotic therapy and analgesic support for three consecutive days. Group-II (06 Goats) - In addition to the routine medicinal treatment protocols, lesions were frozen to -20°C using liquid nitrogen cryotherapy. Cryotherapy found to be advantageous in treating lesions with big size scabs. As the scabs were not removed, they remained at the place providing biological coverings and have helped in early recovery of the lesions. Complications like temporary obstruction of nares, anorexia, sneezing and salivation following cryotherapy were noticed.